Disrupting Y-Box-Binding Protein 1 Function Using OSU-03012 Prevents Endometriosis Progression in In Vitro and In Vivo Models. (January 2017) - Silveira, Cássia G. T.; Marschner, Gabriele; Canny, Geraldine O.; Klocke, Silke; Hunold, Peter; Köster, Frank; Ahrens, Thorben; Rody, Achim; Hornung, Daniela
The objective of the present study was to test the ability of OSU-03012 (2-amino-N-[4-[5-phenanthren-2-yl-3-(trifluoromethyl)pyrazol-1-yl]phenyl]acetamide), a novel and potent celecoxib-derivative, to impair endometriosis progression in in vitro and in vivo models based on its ability to indirectly block Y-box-binding protein 1 (YB-1) function. 12Z human endometriotic epithelial cells and sexually mature female C57BL/6J mice were treated with OSU-03012. Cellular proliferation was quantified by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazoliumbromid assay. Expression of YB-1 and phosphorylated YB-1 in 12Z cells and endometriotic lesions was evaluated by Western blotting and immunohistochemistry (IHC). The IHC for proliferating cell nuclear antigen was performed. OSU-03012 treatment resulted in decreased YB-1 and its phosphorylated form in both in vitro and in vivo models. Endometriotic lesion size was significantly reduced in OSU-03012-treated mice (27.6 ± 4.0 mm 3 ) compared to those from the control group (50.5 ± 6.9 mm 3, P < .0001). A significant reduction in endometriotic epithelial cell proliferation was observed in endometriotic lesions exposed to OSU-03012 treatment ( P = .0346). In conclusion, targeting YB-1 via OSU-03012 showed a potent antiproliferative effect on endometriotic epithelial cells in vitro and in a mouse model of disease.